Safety profile of chlorhexidine and povidone-iodine in rectal mucosa cleansing during prostate biopsy - Pedraza, Adriana M.; Álvarez Villarraga, Jeffer David; Zapata Copete, María Alejandra; Patel, Dhruti; García-Perdomo, Herney Andrés (Frontiers in Urology, 2023)
Objective: To evaluate the use of rectal mucosal cleansings before transrectal ultrasound-guided prostate biopsy (TRUS-PB) with a transrectal approach, comparing the safety profiles of chlorhexidine and povidone-iodine. Methods: We conducted a retrospective analysis of our prospectively maintained database between August 2019 to September 2020 in a high-volume hospital in Colombia. 428 consecutive patients who underwent TRUSPB with a transrectal approach were included in this study. 117 patients received povidone-iodine, and 311 patients received chlorhexidine for rectal mucosa cleansings. We conducted 48-hour, weekly, and 30-day telephone follow-ups following the procedure. The complications were registered in our database. Analysis was performed using STATA 15. Results: There was a statistically significant increased risk of hematuria, urinary retention, and rectal bleeding in those patients exposed to Chlorhexidine (p 0.00006, 0.000008, and 0.01 respectively). We did not find any differences in bacteremia (p 0.18) or urinary tract infection (p 0.77) rates between the groups. Rectal antisepsis with chlorhexidine significantly increased the risk of non-infectious complications (OR: 5.25; 95%IC: 2.17-14.11). Conclusions: In terms of infectious complications, there were no differences between the use of povidone-iodine and chlorhexidine for rectal mucosal cleansing prior to TRUS-PB. Povidone iodine appeared to be a safer option, as it is associated with fewer risks of hematuria, rectal bleeding, and urine retention.